Variation in Gynecologic Aseptic Technique [214]. (May 2015) - Desai, Vrunda Bhavsar; Murdaugh, Kimberly M.; Fan, Linda
Abstract : INTRODUCTION: There are limited data available regarding the optimal protocol for preoperative skin asepsis and the steps of intraoperative patient preparation including draping, Foley, and uterine manipulator placement. Given the lack of a standard process, it is anticipated that these steps are performed in a variety of sequences. METHODS: Between July 2014 and August 2014, preoperative aseptic technique and intraoperative patient preparation were observed for benign gynecologic cases at Yale New Haven Hospital that included the five required steps: vaginal preparation, abdominal preparation, draping, Foley, and uterine manipulator placement. RESULTS: A total of 50 surgical cases were reviewed including 33 surgeons, 15 (45.5%) academic and 18 (54.5%) private faculty. Vaginal preparation using Hibiclens was performed using 4×4 gauze with ring forceps (76%), a free sponge with ring forceps (16%), and preformed preparation sticks (8%). Housestaff performed the majority of preparations (96%), with two members of the surgical team involved in prepping 38%. Wide variation existed in the step sequence. Vaginal preparation was performed as the initial step 96% followed by abdominal preparation as step 2 (70%). Patient draping occurred either as step 3 (56%), step 4 (24%), or step 5 (20%). Foley catheterization was performed as all steps with the majority at step 4 (50%). Uterine manipulator placement occurred as steps 2–5 with the majority as step 5 (54%). CONCLUSION: Wide variation exists in the performance of the preoperative aseptic technique and intraoperative patient preparation for gynecologic procedures and establishing a standard gynecologic preparation protocol is needed.